PENGEMBANGAN APLIKASI PENCARIAN GURU PRIVAT EDITING VIDEO BERBASIS ANDROID - Nurhasan Nugroho; Riduwan Napianto; Imam Ahmad; Wahyu Ariya Saputra (Jurnal informasi dan komputer, 2021)
The teacher (educator) is a guide in carrying out the teaching and learning process. Teachers usually have different tasks such as classroom teachers, subject teachers and private teachers. Private teachers usually provide material or teaching specifically to their students not formally like in school. There are types of private teachers according to the expertise of each teacher, one of which is a private video editing teacher. In Bandar Lampung it is very difficult to find information related to private video editing teachers, causing students who want to find private video editing teachers to find it difficult and time consuming. So in this study developed an Android-based application that can make it easier to find private video editing teachers in Bandar Lampung so that the search for private tutors is easier and faster. This application was developed using the extreme programming (XP) system development method where, this method can be in tune with changes in design and features with flexible handling. Based on usability testing, the average value was 82.5%, and it was in the good category.